The impact of the ECB banking supervision announcements on the EU stock market - Angelo Baglioni; Andrea Monticini; David Peel (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
We study the impact of ECB's supervisory announcements on the Bank Stock index, from 2013 through 2017. Our evidence shows that the news, related to supervisory actions, do have highly significant effects on the market price of banks, contributing to the volatility of the Bank Stock Index for Europe and Italy. Most announcements signal the need to raise more regulatory capital and lead to negative returns in the stock market, thus increasing the cost of raising new capital. Our study is related to previous ones (by Bernanke and Kuttner) focusing on the impact of monetary policy announcements on the stock exchange.
Keywords: G21; G28; 330; Banking Supervision; ECB; GARCH; Stock Market